Antimicrobial Activity of Chromolaena Odorata and Syzygium Aromaticum against multi-drug resistant clinical isolates from diabetic foot ulcer patients: A cross-sectional study - Solomon Wireko; Jacob Amonoo-Neizer; Samuel Nii Boadu; Jessica Neebo; Oumar Ramatu; Jemimah Aggrey Appiah; Elizabeth Akua Baidoo; Ebenezer Senu; Alexander Kwarteng; Mina Ofosu (Scientific African)
Background: Orthodox medicines have not been successful in eliminating most bacteria associated with diabetic foot ulcer (DFU) due to multi-drug resistance. This study, therefore, investigated the antimicrobial activities of Chromolaena odorata and Syzygium aromaticum, known for their potent antimicrobial properties, in controlling drug-resistant bacterial isolates among DFU patients. Methods: In this cross-sectional study, the aqueous and ethanol extracts of Syzygium aromaticum, and Chromoleana odorata were prepared by maceration method, and its antibacterial effect on clinical strains of antibiotic-resistant bacteria including Staphylococcus aureus, Klebsiella pneumoniae, Proteus mirabilis, Streptococcus sp., Escherichia coli, and Pseudomonas aeruginosa were evaluated with microtiter plate method for determining the MIC (Minimum Inhibitory Concentration). Findings: The MIC of Syzygium aromaticum for Klebsiella pneumoniae was determined to be >5000 µg/ml and 2500 ug/ml for aqueous and alcohol extracts respectively, and 5000 µg/ml and 2500 µg/ml for E. coli. Proteus and Pseudomonas aeruginosa had MIC values of 2500 µg/ml and 1250 µg/ml respectively. In comparison, standard antibiotics like ciprofloxacin and gentamicin have MIC values ranging from 500 to 2000 ug/ml against similar strains, highlighting the potential yet relatively higher concentration requirement of the plant extracts. The MIC of alcohol extract of Chromolaena odorata for Pseudomonas aeruginosa and Proteus mirabilis was 2500 µg/ml, while for E. coli and Klebsiella pneumoniae, it was 5000 µg/ml and >5000 ug/ml respectively. Conclusion: Given the positive effects of the two herbal extracts on resistant bacteria isolates, the plants could be used in different pharmaceutical formulations for the prevention and control of infections associated with DFU however, more studies and trials must be carried out, especially on an herbal extract that possesses antimicrobial properties for developing novel antimicrobial medicines for infection treatment among DFU patients.